Development of SETS-Based Interactive E-LKPD Using Liveworksheets on the Topic of Fluid Dynamics in Senior High Schools - Baiq Aryani Novianti; Jumiatul Hasanah; Sapiruddin Sapiruddin; Khaerus Syahidi; Tsamarul Hizbi (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This study aims to develop an interactive E-LKPD (Electronic Student Worksheet) based on the SETS framework (Science, Environment, Technology, and Society) using Liveworksheets for the topic of Dynamic Fluids. The study also investigates the responses of educators and students to the developed E-LKPD. The Research and Development (R&D) method was employed, utilizing the ASSURE model, which includes the following stages: (1) analyzing learner characteristics, (2) determining learning objectives, (3) selecting strategies, media, and materials, (4) utilizing technology, media, and materials in instruction, and (5) involving learner participation in testing the product. The sixth stage, evaluation, was not conducted in this study. Instruments used for data collection included a needs analysis survey (learner characteristics), validation sheets from material and media experts, and response questionnaires from educators and students. Expert validation results showed that the material feasibility was rated at 87% (very valid) and media feasibility at 83% (very valid). A limited trial with educators revealed an average response rate of 89%, categorized as very practical, while the average student response was 78%, categorized as practical.